Gender roles and women’s mental health: their influence on the demand for psychological care - Toribio Caballero, Sandra; Cardenal Hernáez, Violeta; Ávila Espada, Alejandro; Ovejero Bruna, María Mercedes (Anales de Psicología / Annals of Psychology, 2022)
The prevalence of certain diagnoses, such as eating disorders, depression, anxiety, and borderline personality disorder, is higher among women than among men. When it comes to women’s mental health, focusing on social aspects influencing the way women fall ill becomes crucial. Using a sample of 368 women, we studied the classification ability of a number of clinical variables and sociocultural factors (conformity to gender norms) in order to ascertain whether or not women were receiving psychological care and determine the importance of each of the variables when predicting which women were receiving therapy. Our results showed that women were more likely to be receiving psychological treatment when scoring high on certain clinical variables (such as Suicidal Ideation and Borderline Features) and on a number of variables related to conforming to gender norms (Care for Children, Nice in Relationships, and Sexual Fidelity). Therefore, we believe that integrating the gender perspective into educational, health-related, and psychological care programmes is essential so that gender roles can become more diverse and less constricting of people’s potential, resulting in improved health.